Outcomes and feasibility of the short transitional intervention in psychiatry in improving the transition from inpatient treatment to the community: A pilot study. (25th April 2017) - Hegedüs, Anna; Kozel, Bernd; Fankhauser, Niklaus; Needham, Ian; Behrens, Johann
Abstract: Discharge from psychiatric inpatient care is frequently described as chaotic, stressful, and emotionally charged. Following discharge, service users are vulnerable to becoming overwhelmed by the challenges involved in readapting to their home environments, which could result in serious problems and lead to readmission. The short transitional intervention in psychiatry (STeP) is a bridging intervention that includes pre‐ and post‐discharge sections. It aims to prepare patients for specific situations in the period immediately following discharge from a psychiatric hospital. We conducted a quasi‐experimental pilot study to determine the feasibility of the intervention, and gain insight into the effects of the STeP. Two inpatient wards at a Swiss psychiatric hospital participated in the study, and represented the intervention and control arms. Patient recruitment and baseline assessment were performed 2 weeks prior to discharge. Follow‐up data were collected 1 week subsequent to discharge. Questionnaires measured coping, admission and health‐care usage, self‐efficacy, working alliance, experience of transition, and the number of difficulties experienced following discharge. Fourteen and 15 patients completed the follow‐up assessment in the control and intervention groups, respectively. The STeP did not affect primary or secondary outcomes; however, it was shown to be feasible, and patients' feedback highlighted the importance of post‐discharge contact sessions. Further research is required to improve understanding of the discharge experience, identify relevant patient outcomes, and assess the effectiveness of the intervention in an adequately‐powered randomized, controlled trial.